Inside Amy Schumer. The complete series [videorecording (DVD)]. - Schumer, Amy (Comedy Central, Paramount, 2021)
It's finally here: all four seasons of the groundbreaking sketch series, Inside, in one box set. All the sketches, all the guest stars (including Amber Rose, Justin Long and Jon Glaser), and all the best of Amy.